Discerning the supply chain of Bumiputera entrepreneurs in the Malaysian wood products and furniture industry: status, challenges and remedial measures - Amir, Mohd. Afthar; Othman, Kamaruzaman; Ratnasingam, Jegatheswaran; Ab Latib, Hazirah; Jegatheswaran, Natkuncaran; Lim, Choon Liat (North Carolina State University, 2023)
Supply chain management has been identified as the major constraint on the growth of Bumiputera entrepreneurs in the Malaysian wood products and furniture sector. Therefore, a study to examine the characteristics of supply chain among Bumiputera entrepreneurs in the wood industry registered with the Malaysian Timber Industry Board was conducted. The results revealed that most of the respondents were micro- and small-sized enterprises, with a sales focus on the domestic and contract-market. They were predominantly wooden furniture manufacturers, who had a relatively low level of knowledge about supply chain management. The respondents also indicated that their major challenges include lack of finances, small volume of production, and the lack of government support. The factor analysis and regression analysis conducted revealed that for Bumiputera entrepreneurs to gain better supply chain management they need to improve their frequency of engagement, trust, culture, and maturity with their supply chain actors and partners. The results of this study are unique, as it implies that policymakers should take heed of improving supply chain management, to reverse the flagging fortune of Bumiputera entrepreneurs in the Malaysian wood products and furniture sector.